Kemampuan Pemahaman Konsep Matematika Siswa SMP Melalui Model Discovery Learning Dan Model Team Assisted Individualization - Tri Gusti Putra; Ristontowi Ristontowi; Masri Masri (RANGE: Jurnal Pendidikan Matematika, 2023)
This study aims to determine whether there are differences in students' ability to understand mathematical concepts taught using the Discovery Learning model, Cooperative Learning Type Team Assisted Individualization (TAI) model and the conventional model. This type of research was quasi-experimental. The population in this study was the class VIII SMP Negeri 11 Bengkulu City which consisted of six classes, namely class VIII B, VIII C, VIII D, VIII F, VIII G, and VIII H. Samples in this study were three homogeneous classes from six population classes that were randomly selected, namely class VIII B as the experimental class I which was treated with Discovery Learning model, class VIII C as the experimental class II which was treated with Cooperative Learning Type Team Assisted Individualization (TAI) model, and class VIII F as a control class using a conventional model. Based on the results of the research on the ability to understand concepts, shows that there are differences between the Discovery Learning model, the Cooperative Learning Type Team Assisted Individualization (TAI) model, and the conventional model. The post-test scores of the students revealed that the Discovery Learning model outperformed the Cooperative Learning Type Team Assisted Individualization (TAI) model and the conventional model.